Social outcomes following mine closure: an abundance of good intentions undermined by a lack of leverage - Wall, L (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
As expectations around environmental and safety considerations of mine closure have solidified, focus is increasingly shifting towards the goals of and delivery against social aspects of mine closure. Many companies and practitioners cite the goal of achieving a ‘positive legacy’, however, the next level of definition of what this should comprise on an asset-by-asset basis is frequently absent, and questions of how a positive legacy is to be assessed, by whom, and over what time period remain. This paper reports on the results of a business survey developed to understand the drivers for performance in social aspects of closure from an industry perspective. The survey results note the high-level commitments/good intentions stated by companies at both corporate and asset levels, while also highlighting the relative lack of leverage of all parties to influence social aspects of closure. With regulators largely silent on the social outcomes to be achieved through a mine closure process, and communities holding limited leverage to influence decisions at the time of closure, the primary decision makers remain to be companies themselves. In this context, the goal of a ‘positive legacy’ remains largely undefined, provides insufficient clarity for asset level managers, leaving social closure planning vulnerable to budget cuts and shifting goal posts. This paper will argue improved performance in the social outcomes post mine closure requires not more good intentions, but the creation of greater leverage through definition of social closure criteria at an asset level, through enhanced focus on social outcomes in regulation and critically, greater community involvement in the design, implementation and assessment of social outcomes.
Keywords: positive legacy